The sub‐prime crisis, the credit crunch and bank “failure”: An assessment of the UK authorities' response - Hall, Maximilian J.B. (Journal of financial regulation and compliance, 2009)
The purpose of the paper is to explain how UK bank failure resolution policy has evolved since the nationalisation of Northern Rock in February 2008 in the light of the fallout from the sub-prime crisis and the subsequent credit crunch. The evolution of the UK authorities' approach, from a piecemeal approach to a comprehensive, system-wide approach, is traced through analysis of the treatment accorded the troubled entities Alliance and Leicester, HBOS (both the subject of separate officially brokered takeover-rescues) and Bradford and Bingley (eventually nationalised, like Northern Rock) prior to consideration of the two industry-wide bailout schemes introduced in October 2008 and January 2009. Confounding initial hopes, Northern Rock proves to be just the first of a series of major institutional casualties of the fallout from the sub-prime crisis, eventually necessitating a comprehensive and system-wide solution. While this successfully prevents the system from literally collapsing in the Autumn of 2008, in the wake of the decision not to rescue Lehman Brothers in the USA, it fails to stimulate lending, as intended. Accordingly, a second industry bailout package was introduced in January 2009, but even this may fail to secure the main goals of intervention-financial stability and a resuscitation of bank lending to support the ailing economy-heralding possible further state inroads into domestic bank ownership. The paper clearly identifies the need for, and nature of, both the ad hoc and system-wide solutions adopts to deal with individual cases of institutional failure and the wider stability concerns, respectively. The authorities' actions are subject to critical analysis, while a personal assessment of both the House of Commons Treasury Committee's report on Northern Rock and the tripartite authorities' reform proposals, which culminate in the Banking Act of 2009, is also provided.